Effect of a Housing Intervention on Selected Cardiovascular Risk Factors Among Homeless Adults With Mental Illness: 24‐Month Follow‐Up of a Randomized Controlled Trial - Antony Chum; Ri Wang; Rosane Nisenbaum; Patricia O’Campo; Vicky Stergiopoulos; Stephen Hwang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Cardiovascular disease is a leading cause of mortality among people experiencing homelessness. This study investigated whether housing intervention affects cardiovascular disease risk factors among homeless adults with mental illnesses over a 24‐month period. Methods and Results We conducted a randomized controlled trial of a Housing First intervention that provided community‐based scattered‐site housing and support services. Five hundred seventy‐five participants were randomized to the intervention (n=301) or treatment as usual (TAU) (n=274). Analyses were performed according to the intention‐to‐treat principle using generalized estimating equations. There were no differences in change over 24 months between the 2 groups for blood pressure, tobacco, and cocaine/crack use. However, the intervention had an impact on reducing the number of days of alcohol intoxication by 1.58 days compared with TAU (95% CI, −2.88 to −0.27, P=0.0018). Over the 24‐month period, both the intervention and TAU groups had significant reductions in tobacco and cocaine use. Conclusions The intervention, compared with TAU, did not result in greater improvements in many of the selected cardiovascular risk factors. Since the study took place in a service‐rich city with a range of pre‐existing supportive services and universal health insurance, the high level of usual services available to the TAU group may have contributed to reductions in their cardiovascular disease risk factors. Further research is needed to develop interventions to reduce risk factors of cardiovascular disease among people experiencing homelessness and mental illness beyond existing treatments. REGISTRATION www.isrctn.comURL: www.isrctn.com. Unique Identifier: ISRCTN42520374